Application of the principal component analysis–cloud model in the assessment of the seismic stability of slopes - Li, Wei-Wei; Xue, Er-Wei; Gu, Xin-Bao; Yang, Chao; Zhao, Chao (Frontiers in Earth Science, 2024)
The seismic stable assessment of slopes is significant for the slope instability, so the accurate estimation for the seismic stable level of slopes is vital. However, many factors affect the seismic stability of slopes, and its instability has a certain fuzziness and randomness. The principal component analysis-cloud model is introduced at first to assess the seismic stability of slopes. Secondly, the index coefficients are calculated using the principal component analytical method. Then, the characteristic value of the normal cloud model is obtained based on the classification standard of different indexes, and the relevant evaluation model is established. The conclusions are drawn that the method is feasible for the accurate assessment of seismic stability of slopes, and its accuracy is very high. So, a new approach can be provided for the future seismic stability assessment of slopes.